Job Satisfaction among gen Y in Selangor, Malaysia - Harpajan Singh, Tara Singh; Chow, Cheok Keat; Syarifah Mastura, Syed Abu Bakar (INTI International University, 2018)
Managing conflicting views and needs of a diverse workforce in organizations today poses a challenge for many organizations. Managing Gen Y however continues to be an uphill task for many organizations, as these generations are found to be of different paradigms (Lee et al., 2012) and leaders today fail to bring out the best with their millennial talent. As Gen Y are keenly knocking on organization’s doorstep, the findings of this study serves to help employers alike to have a better understanding on what motivates Gen Y in the workplace so as to foster retention. Furthermore, it is understood that organizational turnover at any level is costly. Thus if one can understand the motivators which helps to decrease job dissatisfaction and turnover, then employee needs are allegedly met, whereby leading to increase retention of employees. As such, this study is established to further identify factors that pose an influence on Gen Y in Selangor, Malaysia on the topic of job satisfaction. In addition, variables such as career development opportunities, monetary rewards, working environment, and work/life balance will be further discussed in this literature. The research methodology used would be quantitative methods based on descriptive research. Questionnaires are distributed to respondents that fit into the given criteria as the topic suggests.